Micro/nanoscale biochar facilitates cadmium immobilization and soybean resilience: Insights from microbial life-history strategies and plant physiological response - Yaping Wang; Yichen Xu; Yini Cao; Yi Hu; Changrui Liu; Chuanxin Ma; Wende Yan (Bioresource Technology, 2026)

A fast-response framework for real-time 3D wind field reconstruction: Supporting urban air mobility applications in complex environments - Zihao Pang; Junxia Gu; Quanqian Xu; Shuai Han; Lanxin Luo; Zhiqiang Zhang; Zhi Zhu; Tao Zhang; Yaping Ma; Dongdong Shen (Sustainable Cities and Society, 2026)

A bone-homing DNA tetrahedral framework nucleic acids nanodevice orchestrates osteogenic regeneration to rescue postmenopausal osteoporosis - Qiumei Li; Fenglin Zhou; Shiyi Zeng; Yue Gao; Qian Shen; Yaping Wu; Chuan Ma; Yunfeng Lin; Jingang Xiao; Kui Huang (Chemical Engineering Journal, 2026)

Synergistic salt confinement and dipole-mediated ion regulation in a self-adaptive zwitterionic hydrogel electrolyte for ultrastable zinc anodes and multifunctional ionic sensing - Pengyun Xie; Xin Wang; Wenxin Miao; Yaping Jiang; Guofu Ma; Zhe Zhang; Hui Peng (Chemical Engineering Journal, 2026)

Mechanisms and effects of ozone-pullulanase treatment on multiscale structures and in vitro digestibility of rice starch - Zixuan Liu; Chunfan Guo; Mingyue Chen; Yaping Xu; Jingxuan Ma; Ru Wang; Zhaoxia Wu (Food Chemistry, 2026)

The exosomal bta-miR-1246/ATOH8 signaling axis: A key Regulator of intramuscular adipocytes development and beef marbling - Yaping Song; Dongmei Yang; Chao Jiang; Xiaoyu Song; Ruopu Jiao; Hongfang Gong; Yilun Ma; Sayed Haidar Abbas Raza; Sameer Dinkar Pant; Guijie Zhang; Yun Ma; Linsen Zan; et al. (Food Bioscience, 2026)

Deep learning-enabled real-time acoustofluidic sorting for selective microalgae recovery under wastewater-relevant heterogeneous conditions - Zihan Li; Xian Jiang; Wenzhe Gong; Aoyang Tang; Yan Ma; Xia Du; Yaping Xie; Tielin Shi; Zhiyong Liu; Guanglan Liao; Lei Nie (Bioresource Technology, 2026)

Rhizosphere inoculation with Streptomyces pactum is associated with sugar-related fruit quality and rhizosphere variation in goji berry (Lycium barbarum L.) - Yaping Ma; Jie Cao; Ping Yang; Yusupu Wayiti; Shuo Han; Kelong Wang; Alimire Ailimujiang; Yue Zhang (Plant and Soil, 2026)

Multiscale discrete fracture-matrix method for simulating groundwater flow in fractured geological media - Chen Zuo; Lei Ma; Di Gao; Qiankun Luo; Yaping Deng; Jiazhong Qian (Journal of Hydrology, 2026)

Anomalous contaminant transport in fractured porous media: Insight from asynchronous hydraulic changes in fractures and rock matrix - Lei Ma; Di Han; Qiankun Luo; Yaping Deng; Yunhai Fang; Chao Zhang; Jiazhong Qian (Journal of Contaminant Hydrology, 2026)

From syngas to food - high-moisture extrusion of Clostridium autoethanogenum protein into fibrous meat analogues - Tao Ding; Zhougang Chen; Yuchen Zhao; Hao Wang; Xiaofang Liang; Jie Wang; Jie Yang; Yaping Zhu; Shifeng Ma; Min Xue (Food Research International, 2026)

Analysis of WNT5A as a key regulator of intramuscular fat deposition in muscle-adipocyte co-cultures - Hongfang Gong; Yaping Song; Dongmei Yang; Chao Jiang; Ruopu Jiao; Yilun Ma; Sayed Haidar Abbas Raza; Jiupan Zhang; Dawei Wei (Tissue and Cell, 2026)

Dynamic hydrogen buffer integrated with single Pt sites for enhanced durability of high-temperature proton exchange membrane fuel cells - Yabin Xu; Jing Tian; Li Wang; Jiuli Xia; Yandong Wu; Qie Liu; Jingjing Wang; Shiqian Du; Tingting Han; Miaoyu Li; Zuyao Jiang; Yaping Gu; et al. (Science Bulletin, 2026)

Tetracycline-derived N/P co-doped porous graphene-like carbon for effective removal of tetracycline: Synergistic adsorption-degradation mechanism - Shiye Cai; Chuanze Ma; C. Srinivasakannan; Gang Xue; Li Wang; Yaping Wang; Xinhui Duan (Journal of Environmental Chemical Engineering, 2026)

Synchrony of prehistoric agricultural evolution and drought events in the North China Plain - Yanpeng Li; Shengrui Li; Hai Xu; Keliang Zhao; Guanhan Chen; Yaping Zhang; Jiacheng Ma; Junchi Liu; Yong Ge; Yan Zheng; Xinying Zhou; Xiaoqiang Li (Quaternary Science Reviews, 2026)

Multi-objective Optimization of Sponge City Storage Tank Considering Inlet and Outlet Water Conditions-based on NSGA-II Algorithm - Wang Xiaojuan; Ma Yingqiang; Li Hao; Qin Jie; Xiao Yifei; Yan Yaping; Zhang Tingting; Gao Suxia; Li Jiapeng; Liu Jianlin; Cao Lianbao; Li Wei; et al. (Water Resources Management, 2026)

Heuristic resistance-driven graph approach for preferential flow pathway identification in 3D discrete fracture networks - Lei Ma; Jixian Li; Yaping Deng; Di Han; Haichun Ma; Xuelin Cui; Jiazhong Qian (Journal of Hydrology, 2026)

In-situ fabrication of absorbents with multiscale capillary channels and enhanced thermal conductivity for rapid viscous oil decontamination - Yaping Wang; Chan Ma; Mohamed Mahmoud Nasef; Eleen Dayana Mohamed Isa (Journal of Environmental Chemical Engineering, 2026)

Synthesis of borneol-based cationic copolymer microspheres via a dual strategy of stereochemistry and cationic sterilization for antibacterial coatings - Xiaobing Ma; Xiangbin Sun; Yuanyuan Xie; Rongmin Wang; Yaping Zhang; Yufeng He; Pengfei Song (Journal of Environmental Chemical Engineering, 2026)

Beyond static imaging: A dynamic decision paradigm for robust array-SAR in diverse sensing scenarios - Xiangdong Ma; Xu Zhan; Xiaoling Zhang; Yaping Wang; Jun Shi; Shunjun Wei; Tianjiao Zeng (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Three-dimensional discrete fracture network identification based on deep learning and reversible jump Markov chain Monte Carlo algorithm - Zhenting Sun; Lei Ma; Quan Li; Yaping Deng; Han Qiu; Haichun Ma; Cihai Chen; Yongshuai Yan; Jiazhong Qian (International Journal of Rock Mechanics and Mining Sciences, 2026)

Local actors and urban green development in China's energy-rich regions: a case study of the Shanxi-Shaanxi-Inner Mongolia region - Binkai Zheng; Yongyong Song; Yaping Wang; Siyou Xia; Xiping Yang; Beibei Ma; Dongqian Xue (Applied Geography, 2026)

Multi-modal feature integration from UAV-RGB imagery for high-precision cotton phenotyping: A paradigm shift toward cost-effective agricultural remote sensing - Xiaoyu Zhi; Qiaomin Chen; Yingchun Han; Beifang Yang; Yaru Wang; Fengqi Wu; Shiwu Xiong; Yahui Jiao; Yunzhen Ma; Shilong Shang; Tao Lin; Yaping Lei; et al. (Computers and Electronics in Agriculture, 2025)

Tiered biomimetic polydimethylsiloxane coated polyurethane sponge for sustainable seawater nanoplastic removal - Yuxin Zheng; Yuanyuan Luo; Shengjia Ma; Shuai Tang; Chengjin Cao; Yaping Zhao (Journal of Hazardous Materials, 2025)

Heteroprotein complex co-aggregation of ovalbumin and ovotransferrin: structure formation and thermodynamics - Yaping Liu; Chenxin Huang; Jiajie Wang; Xianchao Feng; Meihu Ma (Food Hydrocolloids, 2025)

Soil and enzymatic C:N:P stoichiometry response to carbon and nutrient input: evidence from long-term fertilization experiments - Qiong Xiao; Yaping Huang; Guoping Chen; Kailou Liu; Yu Jiang; Boku Zhou; Ping Zhu; Xiaori Han; Junyong Ma; Shutang Liu; Shaomin Huang; Aijun Zhang; et al. (Plant and Soil, 2025)

Corrigendum to “Lysosomal signaling in adipogenesis regulation: A novel pathway to enhance marbled beef quality” [Food Bioscience 68 (2025) 106447] - Xiaoyu Song; Jiupan Zhang; Yaping Song; Chao Jiang; Sayed Haidar Abbas Raza; Sameer Dinkar Pant; Yun Ma; Yanfen Ma; Guijie Zhang; Linsen Zan; Dawei Wei (Food Bioscience, 2025)

Impact of transient flow on bimolecular reactive transport in varying-aperture fractures - Yajing Liu; Jiazhong Qian; Yong Liu; Lei Ma; Yaping Deng; Hailong Chen (Journal of Hydrology, 2025)

Transcriptional repression of CYP26B1 by EBF2 activates retinol metabolic pathway: A strategy to enhance lipid storage and marbling potential of beef - Yaping Song; Chenglei Song; Jiupan Zhang; Dongmei Yang; Chao Jiang; Ruopu Jiao; Hongfang Gong; Yilun Ma; Sayed Haidar Abbas Raza; Sameer Dinkar Pant; Yun Ma; Guijie Zhang; et al. (Food Bioscience, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Self-adapting deflection contact effect for rock fracture deformation - Haichun Ma; Yanan Wang; Yang Xu; Jiazhong Qian; Yaping Deng (Acta Geophysica, 2025)

Integrated harvest and distribution scheduling of fresh agricultural products for multiple farms using a Q-learning-based artificial bee colony algorithm with problem knowledge - Xiaomeng Ma; Xujin Pu; Yaping Fu; Yuan Wang (Swarm and Evolutionary Computation, 2025)

Boosting arsenic removal with metastable Fe2+/Mn3+ redox process in MnFe2O4/rGO composites for high capacity and stability - Tao Zhang; Shengjia Ma; Du Chen; Qingsheng Wu; LiKun Pan; Jiang Xu; Yaping Zhao (Journal of Hazardous Materials, 2025)

Plasma-catalytic reforming of CO2–CH4 over nickel-based catalysts: Catalyst design, plasma activation, and comparison of different catalytic systems - Tian Chang; Xuanchen Chang; Zuotong Zhao; Chuanlong Ma; Xiangen Zhao; Yaping Du; Antonio Otavio T. Patrocinio; Anton Nikiforov; Chuanyi Wang (Journal of Environmental Chemical Engineering, 2025)

Lysosomal signaling in adipogenesis regulation: A novel pathway to enhance marbled beef quality - Xiaoyu Song; Jiupan Zhang; Yaping Song; Chao Jiang; Sayed Haidar Abbas Raza; Sameer Dinkar Pant; Yun Ma; Yanfen Ma; Guijie Zhang; Linsen Zan; Dawei Wei (Food Bioscience, 2025)

Biochar and PGPR Influence Rhizosphere Bacteria and Synergistically Regulate Tomato Seedling Biomass Under Greenhouse Conditions - Zhenlu Yan; Yuyuan Xing; Changli Ma; Xin Li; Yaping Duan; Xue Wang; Minghao Liu; Muhammad Khashi u Rahman; Xingang Zhou (Journal of Soil Science and Plant Nutrition, 2025)

Development and research progress of microalgae as a production platform for antimicrobial peptides - Qiaolei Wang; Yuyang Ma; Fengjie Sun; Kang Wang; Jinju Ma; Bingkui Zhu; Kai Cao; Yaping Shao; Yulin Cui; Hao Zhang; Yuyong Wu; Chunxiao Meng; et al. (Journal of Applied Phycology, 2025)

Deep learning-based inversion framework for fractured media characterization by assimilating hydraulic tomography and thermal tracer tomography data: Numerical and field study - Cihai Chen; Yaping Deng; Jiazhong Qian; Haichun Ma; Lei Ma; Jichun Wu; Hui Wu (Engineering Geology, 2025)

Stochastic modeling of discrete fracture network considering spatial pattern and variability of fracture distribution - Di Gao; Lei Ma; Jiazhong Qian; Qiankun Luo; Haichun Ma; Yaping Deng; Xiaosan Yan (Geosciences Journal, 2025)

Enzymatic degradation of mycotoxin patulin by a short-chain dehydrogenase/reductase from Bacillus subtilis and its application in apple juice - Jiafeng Niu; Bin Ma; Juan Shen; Hao Zhu; Yaping Lu; Zhaoxin Lu; Fengxia Lu; Ping Zhu (Food Microbiology, 2025)

Polyanionic hydrogel electrolytes applied to interface-stabilized zinc ion hybrid capacitors - Pengyun Xie; Xin Wang; Yaping Jiang; Ying Tang; Kaifa Dong; Hui Peng; Guofu Ma; Ziqiang Lei (Chemical Engineering Journal, 2025)

Rainfall intensities determine accuracy of canopy interception simulation using the Revised Gash model - Mengliang Ma; Qiang Li; Yaping Wang; Jin Liang; Jiangyao Wang; Jinliang Liu; Mingfang Zhang (Agricultural and Forest Meteorology, 2025)

Development of the CMA-ChemRA: China Regional Weakly Coupled Chemical-Weather Reanalysis System with product since 2007 - Tao Zhang; Zijiang Zhou; Zhisen Zhang; Junting Zhong; Zhiquan Liu; Xiaoye Zhang; Wenhui Xu; Lipeng Jiang; Jie Liao; Yaping Ma; Yike Zhou; Huiying Wang; et al. (Science of The Total Environment, 2024)

Multi-omics integration analysis reveals metabolic regulation of carbohydrate and secondary metabolites during goji berry (Lycium barbarum L.) maturation - Yaping Ma; Mura Jyostna Devi; Lihua Song; Handong Gao; Lei Jin; Bing Cao (Postharvest Biology and Technology, 2024)

Association Between Neuroinflammation and Parkinson’s Disease: A Comprehensive Mendelian Randomization Study - YiNi Wang; XinYu Shi; YaPing Yin; Fei Yang; YiNan Zhang; Xin He; Da Wen; Bai-Xiang Li; Kun Ma (Molecular Neurobiology, 2024)

Enhanced reductive catalytic fractionation of lignocellulose using a water-resistant RuNiZnOx/Nb2O5 catalyst with synergistic hydrogen spillover and acidic properties - Zhaozhuo Yu; Wenzhuo Kong; Yaping Guo; Wen Liang; Jiawei Liang; Meijuan Chen; Dongxu Zhao; Hongzhen Ma; Xiangjun Liu; Solomon Inalegwu Okopi; Lei Che; Qi Zhang; et al. (Fuel, 2024)

Upcycling polystyrene microplastics to Fe/Mo-doped sponge-carbon: Mo5+ enhanced electron transfer for boosting Fenton-like performance - Shengjia Ma; Shuai Tang; Yaping Zhao (Chemical Engineering Journal, 2024)

Deep eutectic solvent microemulsions with abundant hydrogen ions in supercritical CO2 for decontamination of radioactive solid waste: Overcoming roadblocks to hydrogen ions deficiency - Huitao Lv; Jianzhang Gao; Jiaqi Chen; Tianyu Li; Chao Peng; Yaping Li; Fuqiu Ma; Yun Xue; Yongde Yan; Emmanuel Osei Tutu (Chemical Engineering Journal, 2024)

Carrier effects of face mask-derived microplastics on metal ions: Enhanced adsorption by photoaging combined with biofilms, exemplified with Pb(Ⅱ) - Shuai Tang; Shengjia Ma; Lujian Lin; Yimei Ding; Xiaoting Zhang; Xiaowei Wu; Qun Zhang; Md. Nahid Pervez; Chengjin Cao; Yaping Zhao (Journal of Hazardous Materials, 2024)

Analysis of the Relationship Between Parkinson’s Disease and Diabetic Retinopathy Based on Bioinformatics Methods - XinYu Shi; YiNi Wang; YaPing Yin; Fei Yang; YiNan Zhang; Xin He; Da Wen; Kun Ma; Bai-Xiang Li (Molecular Neurobiology, 2024)

What drives equipment manufacturing enterprises green technology innovation in the Yangtze River Economic Belt? A configuration analysis based on DEA-fsQCA model - Na Zhao; Dalai Ma; Yaping Xiao; Bitan An; Jiawei Zhang (Process Safety and Environmental Protection, 2024)

Low-humidity sensor and biomimetic power supply based on mesoporous silica/polymerizable deep eutectic solvent ionogels - Zhiyan Ma; Yanyu Cui; Yaping Song; Yunlong Yu; Hongran Zhao; Sen Liu; Xishuang Liang; Teng Fei; Tong Zhang (Chemical Engineering Journal, 2024)

Research on the spatiotemporal evolution and influencing factors of urbanization and carbon emission efficiency coupling coordination: From the perspective of global countries - Dalai Ma; Yin Yan; Yaping Xiao; Fengtai Zhang; Haoran Zha; Ruonan Chang; Jiawei Zhang; Zuman Guo; Bitan An (Journal of Environmental Management, 2024)

Study on the shale fracture geometry influence on nonlinear gas seepage behavior - Peng Zhou; Haichun Ma; Jiazhong Qian; Xianfa Wei; Yaping Deng (Gas Science and Engineering, 2024)

Efficient production of R-2-(4-hydroxyphenoxy) propionic acid by Beauveria bassiana using biofilm-based two-stage fermentation - Shuping Zou; Yizhi Ma; Wei Ding; Yongkang Jiang; Xiaomin Chen; Juan Chen; Hailing Gao; Yaping Xue; Yuguo Zheng (Bioresource Technology, 2024)

Multi-objective migrating birds optimization for solving stochastic home health care routing and scheduling problems considering caregiver working time constraints - Yaping Fu; Xiaomeng Ma; Kaizhou Gao; Hongfeng Wang; Ali Sadollah; L.Y. Chen (Swarm and Evolutionary Computation, 2024)

Characterization of discrete fracture networks with deep-learning based hydrogeophysical inversion - Yaping Deng; Xueyuan Kang; Haichun Ma; Jiazhong Qian; Lei Ma; Qiankun Luo (Journal of Hydrology, 2024)

Different ligand functionalized bimetallic (Zr/Ce)UiO-66 as a support for immobilization of phosphotungstic acid with enhanced activity for the esterification of fatty acids - Qiuyun Zhang; Yaping Wu; Xingyue Hong; Zhenying Li; Yanting Lei; Rongfei Yu; Taoli Deng; Yutao Zhang; Peihua Ma (Sustainable Chemistry and Pharmacy, 2024)

Identification of high-permeability and water-rich zones in a fractured karst water source area based on the hydraulic tomography method - Lei Ma; Xiaofan Sun; Jiazhong Qian; Wei Wang; Yaping Deng; Yunhai Fang (Journal of Hydrology, 2024)

Infection of postharvest pear by Penicillium expansum is facilitated by the glycoside hydrolase (eglB) gene - Meiqiu Xu; Esa Abiso Godana; Jingyu Li; Yaping Deng; Yufei Ma; Huiyuan Ya; Hongyin Zhang (International Journal of Food Microbiology, 2024)

Constructing a cross-field scenario system to aware systemic risk: national security as an example - Qing Deng; Mengjiao Yao; Hui Zhang; Feng Yu; Lida Huang; Yaping Ma (Natural Hazards, 2024)

Spatiotemporal evolution and influencing factors of water resource green efficiency in the cities of the Yangtze River Economic Belt - Dalai Ma; Bitan An; Jiawei Zhang; Fengtai Zhang; Yaping Xiao; Zuman Guo (Environmental Science and Pollution Research, 2023)

Superior solar water purification achieved by the excellent photothermal conversion and thermal management of porous plasmonic TiN nanoparticles - Yaping Gao; Xiaojie Zhou; Nuo Fu; Sihua Su; Baopeng Ma; Qifeng Ruan; Di Wu; Nan Zhang; Ziwei Deng; Ruibin Jiang (Chemical Engineering Journal, 2023)

ALPK1 Expressed in IB4-Positive Neurons of Mice Trigeminal Ganglions Promotes MIA-Induced TMJ pain - Taomin Zhu; Huimin Li; Yuxiang Chen; Xueke Jia; Xiaohan Ma; Xin Liu; Yaping Feng; Jin Ke (Molecular Neurobiology, 2023)

Study on the seepage mechanisms of rock with bifurcation fractures under confining pressure - Haichun Ma; Peichao Feng; Jiazhong Qian; Yaping Deng; Daoxiang Wu (Hydrogeology Journal, 2023)

Phosphate functionalized silicide for efficient removal of uranium contamination from hypersaline effluents at ultralow dosage - Yaping Jian; Yue Ma; Meng Cao; Shilei Zhao; Qin Peng; Hui Wang; Tao Liu; Yihui Yuan; Ning Wang (Chemical Engineering Journal, 2023)

Catalytic activity and anti-passivation of single iron atoms and atomic clusters co-stabilized on carbonized waste polystyrene plastic - Shengjia Ma; Shuai Tang; Tao Zhang; Wei Jin; Hui Zhu; Yaping Zhao; Dionysios D. Dionysiou (Chemical Engineering Journal, 2023)

HIF-1α–PPARγ–mTORC1 signaling pathway-mediated autophagy induces inflammatory response in pancreatic cells in rats with hyperlipidemic acute pancreatitis - Yumei Ma; Xiaolin Li; Zhilan Liu; Xiaohong Xue; Yaping Wang; Yingcai Ma (Molecular Biology Reports, 2023)

Fine and coarse particulate air pollution and out-of-hospital cardiac arrest onset: a nationwide case-crossover study in China - Chang Pan; Chang Xu; Jiaqi Zheng; Ruixue Song; Chuanzhu Lv; Guoqiang Zhang; Huiqiong Tan; Yu Ma; Yimin Zhu; Xiaotong Han; Chaoqian Li; Shengtao Yan; et al. (Journal of Hazardous Materials, 2023)

Au loaded mesoporous SiO2/gelatin hydrogel: Detecting low humidity and NH3 - Zhiyan Ma; Yunlong Yu; Ke Wu; Yaping Song; Sen Liu; Xi Yang; Teng Fei; Tong Zhang (Chemical Engineering Journal, 2023)

Visualize intracellular β-galactosidase using an asymmetric near-infrared fluorescent probe with a large Stokes shift - Shijun Chen; Xiaodong Ma; Haijie Wang; Lin Wang; Yuanyuan Wu; Yaping Wang; Yiyi Li; Wenkang Fan; Caoyuan Niu; Shicong Hou (Analytica Chimica Acta, 2023)

Mesoscopic study of seepage characteristics with shear displacement in a single fracture - Peichao Feng; Haichun Ma; Jiazhong Qian; Yaping Deng (Acta Geophysica, 2023)

What were the spatiotemporal evolution characteristics and the influencing factors of urban land green use efficiency? A case study of the Yangtze River Economic Belt - Dalai Ma; Jiawei Zhang; Fengtai Zhang; Yaping Xiao; Hongmei Tan; Zuman Guo; Bitan An (Environmental Monitoring and Assessment, 2023)

Spatiotemporal differentiation of carbon emission efficiency and influencing factors: From the perspective of 136 countries - Yaping Xiao; Dalai Ma; Fengtai Zhang; Na Zhao; Ling Wang; Zuman Guo; Jiawei Zhang; Bitan An; Yuedong Xiao (Science of The Total Environment, 2023)

Numerical evaluation of the suitability of the equivalent porous medium model for characterizing the two-dimensional flow field in a fractured geologic medium - Lei Ma; Di Han; Jiazhong Qian; Di Gao; Haichun Ma; Yaping Deng; Xiaoliang Hou (Hydrogeology Journal, 2023)

Sorption of bisphenol A onto microplastics and associated environmental risks in comparison to engineered carbonous materials and natural media - Shuai Tang; Shengjia Ma; Tao Zhang; Xuemin Liu; Md. Nahid Pervez; Chengjin Cao; Yaping Zhao (Gondwana Research, 2023)

Enhanced arsenite removal from water using zirconium-ferrocene MOFs coupled with peroxymonosulfate:oxidation and multi-sites adsorption mechanism - Zongchen Li; Shengjia Ma; Linfeng Sang; Guojuan Qu; Tao Zhang; Bin Xu; Wei Jin; Yaping Zhao (Chemosphere, 2023)

Prenatal BPA exposure disrupts male reproductive functions by interfering with DNA methylation and GDNF expression in the testes of male offspring rats - Yaping Mao; Dan Li; Qiaoqiao Yang; Xiucong Pei; Zhiwen Duan; Mingyue Ma (Environmental Science and Pollution Research, 2023)

Interferon-τ -induced ISG15-AS regulates endometrial receptivity during early goat pregnancy - Ruixue Zhang; Xinyan Guo; Hanbing Li; Zuhui Li; Suhua Gong; Haijing Li; Yongjie Ma; Haokun Liu; Chuxi Gao; Aihua Wang; Yaping Jin; Pengfei Lin (Theriogenology, 2023)

A chromosome-level genome assembly reveals that tandem-duplicated CYP706V oxidase genes control oridonin biosynthesis in the shoot apex of Isodon rubescens - Yuwei Sun; Jie Shao; Haili Liu; Hua Wang; Guangyi Wang; Jianhua Li; Yaping Mao; Zhuo Chen; Ke Ma; Lin Xu; Yong Wang (Molecular Plant, 2023)

Improved thermal tolerance of ovotransferrin against pasteurization by phosphorylation - Yaping Liu; Jiajie Wang; Chenxin Huang; Bingying Cai; Fuxuan Guo; Lin Chen; Xianchao Feng; Meihu Ma (Food Chemistry, 2023)

Quantification of solute transport in a fracture-matrix system using geoelectrical monitoring - Yongshuai Yan; Jiazhong Qian; Lei Ma; Guizhang Zhao; Yaping Deng; Haoming Zhang; Yunhai Fang; Yong Liu (Journal of Hydrology, 2023)

Multiscale fractures integrated equivalent porous media method for simulating flow and solute transport in fracture-matrix system - Lei Ma; Di Gao; Jiazhong Qian; Di Han; Kun Xing; Haichun Ma; Yaping Deng (Journal of Hydrology, 2023)

Structural elucidation of a novel polysaccharide from Ophiopogonis Radix and its self-assembly mechanism in aqueous solution - Bei Wang; Bin Huang; Bing Yang; Liang Ye; Jingqi Zeng; Zhiwei Xiong; Yaping Chen; Shuchen Guo; Yanjun Yang; Weikun Ma; Maomao Zhu; Xiaobin Jia; et al. (Food Chemistry, 2023)

Characterizing seasonal recharge between a river and shallow aquifer in a floodplain based on time-lapse electrical resistivity tomography - Yongshuai Yan; Yaping Deng; Lei Ma; Guizhang Zhao; Jiazhong Qian (Hydrogeology Journal, 2023)

The interfacial behaviors of different arsenic species on polyethylene mulching film microplastics: Roles of the plastic additives - Shuai Tang; Peipei Sun; Shengjia Ma; Wei Jin; Yaping Zhao (Journal of Hazardous Materials, 2023)

Strict rule-based automatic training data extraction using Mobile laser scanning in urban area - Zhenyu Ma; Sander Oude Elberink; Yaping Lin; Panpan Xu; Binbin Xiang; Barbara Koch; Holger Weinacker (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Hydrofacies simulation based on transition probability geostatistics using electrical resistivity tomography and borehole data - Lei Ma; Hui Deng; Yongshuai Yan; Yaping Deng; Weidong Zhao; Xiaohui Tan; Jiazhong Qian (Hydrogeology Journal, 2022)

How industrial water resources green efficiency varies in China: a case study of the Yangtze River Economic Belt considering unexpected output - Dalai Ma; Fengtai Zhang; Yaping Xiao; Lei Gao; Hongbo Liao; Na Zhao; Yuedong Xiao; Xingyu Yang; Wenli Wu (Environment, Development and Sustainability, 2022)

Improving pre-harvest sprouting resistance in rice by editing OsABA8ox using CRISPR/Cas9 - Kai Fu; Weihan Song; Cheng Chen; Changling Mou; Yunshuai Huang; Fulin Zhang; Qixian Hao; Ping Wang; Tengfei Ma; Yaping Chen; Ziyan Zhu; Min Zhang; et al. (Plant Cell Reports, 2022)

Enhanced Influenza Immunity by Nasal Mucosal Administration of the TPGS-Modified Liposomal Vaccine - Shijie Ma; Rui Yu; Yaping Mai; Na Yu; Ting Gao; Jianhong Yang (AAPS PharmSciTech, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Candidate gene analysis of watermelon stripe pattern locus ClSP ongoing recombination suppression - Zhen Yue; Rongxue Ma; Denghu Cheng; Xing Yan; Yaping He; Chunxia Wang; Xiaona Pan; Lijuan Yin; Xian Zhang; Chunhua Wei (Theoretical and Applied Genetics, 2021)

Nanocrystals for Improving Oral Bioavailability of Drugs: Intestinal Transport Mechanisms and Influencing Factors - Zonghua Tian; Yaping Mai; Tingting Meng; Shijie Ma; Guojing Gou; Jianhong Yang (AAPS PharmSciTech, 2021)

Effects of Exogenous Application of GA4+7 and NAA on Sugar Accumulation and Related Gene Expression in Peach Fruits During Developing and Ripening Stages - Xiongwei Li; Pan Liu; Jingyi Zhou; Mingshen Su; Yaping Ma; Huijuan Jia; Jihong Du; Zhongshan Gao; Zhengwen Ye (Journal of Plant Growth Regulation, 2021)

Characterizing temporal behavior of a thermal tracer in porous media by time-lapse electrical resistivity measurements - Ze Yang; Yaping Deng; Jiazhong Qian; Rui Ding; Lei Ma (Hydrogeology Journal, 2021)

Two novel compounds from green walnut husks ( Juglans mandshurica Maxim.) - Hong Yang; Chunli Gan; Yaping Guo; Liyuan Qu; Shuang Ma; Yanbin Ren; Xingwen Wang; Libo Wang; Jian Huang; Jinhui Wang (Natural Product Research, 2020)

The Beneficial Effects of Aluminum on the Plant Growth in Camellia japonica - Yuanjiao Liu; Jingyu Tao; Jing Cao; Yaping Zeng; Xi Li; Jun Ma; Zhuo Huang; Mingyan Jiang; Lingxia Sun (Journal of Soil Science and Plant Nutrition, 2020)

Introduction of a multicenter online database for non-metastatic breast cancer in China - Yaping Yang; Jieqiong Liu; Min Peng; Fengxi Su; Xiaoming Xie; Zhenzhen Liu; Jundong Wu; Wei Wei; Dongxian Zhou; Weiwen Li; Ailing Zhang; Guosen Su; et al. (Science China Life Sciences, 2020)

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

MiR-19a mediates the negative regulation of the NF-κB pathway in lipopolysaccharide-induced endometritis by targeting TBK1 - Nannan Yin; Yaping Yang; Xiaoyan Wang; Chao Yang; Xiaofei Ma; Aftab Shaukat; Gan Zhao; Ganzhen Deng (Inflammation Research, 2019)

Detecting Alpha Synuclein Seeding Activity in Formaldehyde-Fixed MSA Patient Tissue by PMCA - Katelyn Becker; Xinhe Wang; Kayla Vander Stel; Yaping Chu; Jeffrey Kordower; Jiyan Ma (Molecular Neurobiology, 2018)

Probiotics decrease depressive behaviors induced by constipation via activating the AKT signaling pathway - Nana Xu; Wenting Fan; Xiaoyan Zhou; Yaping Liu; Ping Ma; Suhua Qi; Bing Gu (Metabolic Brain Disease, 2018)

The AP2/ERF transcription factor CmERF053 of chrysanthemum positively regulates shoot branching, lateral root, and drought tolerance - Jing Nie; Chao Wen; Lin Xi; Suhui Lv; Qingcui Zhao; Yaping Kou; Nan Ma; Liangjun Zhao; Xiaofeng Zhou (Plant Cell Reports, 2018)

Spatial and temporal precipitation patterns characterized by TRMM TMPA over the Qinghai-Tibetan plateau and surroundings - Ziqiang Ma; Yaping Xu; Jie Peng; Qiuxiao Chen; Dan Wan; Kang He; Zhou Shi; Hongyi Li (International Journal of Remote Sensing, 2018)

Molecular cytogenetic and genomic analyses reveal new insights into the origin of the wheat B genome - Wei Zhang; Mingyi Zhang; Xianwen Zhu; Yaping Cao; Qing Sun; Guojia Ma; Shiaoman Chao; Changhui Yan; Steven S. Xu; Xiwen Cai (Theoretical and Applied Genetics, 2018)

LINGO-1-Fc-Transduced Neural Stem Cells Are Effective Therapy for Chronic Stage Experimental Autoimmune Encephalomyelitis - Xing Li; Yuan Zhang; Yaping Yan; Bogoljub Ciric; Cun-Gen Ma; Jeannie Chin; Mark Curtis; Abdolmohamad Rostami; Guang-Xian Zhang (Molecular Neurobiology, 2017)

Quantitative proteomics analysis reveals the tolerance of Mirabilis jalapa L. to petroleum contamination - Shuisen Chen; Hui Ma; Zhifu Guo; Yaping Feng; Jingwei Lin; Menghua Zhang; Ming Zhong (Environmental Science and Pollution Research, 2017)

NO is involved in spermidine-induced drought tolerance in white clover via activation of antioxidant enzymes and genes - Dandan Peng; Xiaojuan Wang; Zhou Li; Yan Zhang; Yan Peng; Yaping Li; Xiaoshuang He; Xinquan Zhang; Xiao Ma; Linkai Huang; Yanhong Yan (Protoplasma, 2016)

ace-3 plays an important role in phoxim resistance in Caenorhabditis elegans - Yan Han; Shaojuan Song; Yaping Guo; Jianzhen Zhang; Enbo Ma (Ecotoxicology, 2016)

High-level expression and characterization of a thermophilic β-mannanase from Aspergillus niger in Pichia pastoris - Shi Yu; Zhezhe Li; Yaping Wang; Wanping Chen; Lin Fu; Wei Tang; Chen Chen; Yunyun Liu; Xue Zhang; Lixin Ma (Biotechnology Letters, 2015)

A Rosa canina WUSCHEL-related homeobox gene, RcWOX1, is involved in auxin-induced rhizoid formation - Bin Gao; Chao Wen; Lusheng Fan; Yaping Kou; Nan Ma; Liangjun Zhao (Plant Molecular Biology, 2014)

FLT3 and CDK4/6 inhibitors: Signaling mechanisms and tumor burden in subcutaneous and orthotopic mouse models of acute myeloid leukemia - Yaping Zhang; Cheng-Pang Hsu; Jian-Feng Lu; Mita Kuchimanchi; Yu-Nien Sun; Ji Ma; Guifen Xu; Yilong Zhang; Yang Xu; Margaret Weidner; Justin Huard; David Z. D’Argenio (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

Changes to Cuticle Surface Ultrastructure and Some Biological Functions in the Nematode Caenorhabditis Elegans Exposed to Excessive Copper - Shaojuan Song; Yaping Guo; Xiaomin Zhang; Xueyao Zhang; Jianzhen Zhang; Enbo Ma (Archives of Environmental Contamination and Toxicology, 2014)

Callus induction and shoot organogenesis from anther cultures of Curcuma attenuata Wall - Yaping Kou; Guohua Ma; Jaime A. Teixeira da Silva; Nian Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

The complete mitochondrial genome of the butterfly Apatura metis (Lepidoptera: Nymphalidae) - Min Zhang; Xinping Nie; Tianwen Cao; Juping Wang; Tao Li; Xiaonan Zhang; Yaping Guo; Enbo Ma; Yang Zhong (Molecular Biology Reports, 2012)

Vitreoscilla Hemoglobin (VHb) Overexpression Increases Hypoxia Tolerance in Zebrafish (Danio rerio) - Bo Guan; Hong Ma; Yaping Wang; Yuanlei Hu; Zhongping Lin; Zuoyan Zhu; Wei Hu (Marine Biotechnology, 2011)

Population genetic structure and phylogeographical pattern of rice grasshopper, Oxya hyla intricata, across Southeast Asia - Tao Li; Min Zhang; Yanhua Qu; Zhumei Ren; Jianzhen Zhang; Yaping Guo; K. L. Heong; Bong Villareal; Yang Zhong; Enbo Ma (Genetica, 2011)

The application of geostatistics in grain size trend analysis: A case study of eastern Beibu Gulf - Fei Ma; Yaping Wang; Yan Li; Changjiang Ye; Zhiwei Xu; Fan Zhang (Journal of Geographical Sciences, 2010)

A quick isolation method for mutants with high lipid yield in oleaginous yeast - Jufang Wang; Renmin Li; Dong Lu; Shuang Ma; Yaping Yan; Wenjian Li (World Journal of Microbiology and Biotechnology, 2009)

Genetic Variation and Population Structure of Oriental Migratory Locust, Locusta migratoria manilensis, in China by Allozyme, SSRP-PCR, and AFLP Markers - Xianyun Zheng; Yang Zhong; Yihao Duan; Chunxuan Li; Li Dang; Yaping Guo; Enbo Ma (Biochemical Genetics, 2006)

Opioid activity of synthetic deltorphin II analogues and their spin labeled derivatives - Dingjian Yang; Rui Wang; Yaping Ma; Yujun Di; Xiaofeng Huo (International Journal of Peptide Research and Therapeutics, 1999)